2020
DOI: 10.1186/s13049-020-00741-w
|View full text |Cite
|
Sign up to set email alerts
|

Changing role of EMS –analyses of non-conveyed and conveyed patients in Finland

Abstract: Background: Emergency Medical Services (EMS) and Emergency Departments (ED) have seen increasing attendance rates in the last decades. Currently, EMS are increasingly assessing and treating patients without the need to convey patients to health care facility. The aim of this study was to describe and compare the patient casemix between conveyed and non-conveyed patients and to analyze factors related to non-conveyance decision making. Methods: This was a prospective study design of EMS patients in Finland, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 34 publications
2
49
1
2
Order By: Relevance
“…Emergency Medical Services (EMSs) and emergency departments (EDs) have reported increased workload [1,2], mainly due to an aging population and difficulties accessing primary care [2]. The role of the EMS has changed to include more non-critical emergency patients [3], and patients are increasingly assessed and treated at the scene by EMSs, avoiding unnecessary conveyance to EDs [4]. Reported non-conveyance rates substantially vary internationally, between 3.7 and 93.7% in the general population [5]; in Finland, the rate is approximately 40% [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emergency Medical Services (EMSs) and emergency departments (EDs) have reported increased workload [1,2], mainly due to an aging population and difficulties accessing primary care [2]. The role of the EMS has changed to include more non-critical emergency patients [3], and patients are increasingly assessed and treated at the scene by EMSs, avoiding unnecessary conveyance to EDs [4]. Reported non-conveyance rates substantially vary internationally, between 3.7 and 93.7% in the general population [5]; in Finland, the rate is approximately 40% [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the EMS has changed to include more non-critical emergency patients [3], and patients are increasingly assessed and treated at the scene by EMSs, avoiding unnecessary conveyance to EDs [4]. Reported non-conveyance rates substantially vary internationally, between 3.7 and 93.7% in the general population [5]; in Finland, the rate is approximately 40% [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review that included studies from North America, Europe, Australia, Asia, and Africa reported that non-transport rates varied from 4% to 94% [7]. Other studies have found non-transport rates of 40% in Finland [14], 38% in the UK [15], 26.2% in Netherlands [16], 15.5% in Australia [8], 13.8% in Sweden [17], and 12.9% in Denmark [18]. Comparatively, the non-transport rate in our study is low.…”
Section: Occurrence Of Non-transport Ambulance Missionsmentioning
confidence: 99%
“…By its very nature, the ambulance service constitutes a high-risk patient safety environment which provides round-the-clock, year-round care services to a large volume of patients with a wide range of medical complaints [1]. Patients who are not transported to the hospital after an initial assessment by ambulance clinicians, that is, non-conveyed patients in the ambulance service [2], represent a signi cant and increasing proportion of those who seek ambulance services [3][4][5]. The research on patient outcome following non-conveyance is relatively sparse and, to some extent, has contrasting results [6][7][8].…”
Section: Introductionmentioning
confidence: 99%